A COMPARISON BETWEEN A TERRORIST LEADER AND A LONE-WOLF OPERATIVE IN BANGLADESH - Islam, Fatema (Journal of Terrorism Studies, 2023)
The article compares the biography and terrorist portrait of two terrorists of Bangladesh: Mufti Abdul Hannan, a pioneer leader of the prominent terrorist organization Huji-B, and a lone wolf operative named Faizul Hasan. The study reveals the existence of the multifaceted dynamics of the leader (Mufti) and lone wolf (Faizul) encompassing organizational affiliation, operational independence, radicalization processes, motivations, objectives, and the scale of their operations. The study also finds that the pattern of operation of a terrorist leader (Mufti) and the lone wolf terrorist (Faizul) differed significantly in terms of planning, execution, and level of organizational support. While the terrorist leader planned and coordinated activities within a structured group, the lone wolf operated independently, planning and executing actions without coordination with others. Mufti was capable of planning and executing large-scale operations, utilizing the manpower and resources of the organization while Faizul was engaged in smaller-scale operations due to limited resources and the lack of organizational backing. The most important measure of countering terrorist leaders is intelligence gathering to understand the organizational structure and communication channel. In contrast, enhancing monitoring of online platforms to identify the signs of radicalization and raising awareness are the key measures for countering lone-wolf terrorists.